The Implementation of Knowledge Management System (KMS) Evaluation Model in Improving Employee Performance: A Case Study of the State Electricity Company - Wahyu Budianto; Wahyu Sardjono (ComTech: Computer, Mathematics and Engineering Applications, 2022)
Employee performance has a crucial role in running a company. Thus, efforts to improve employee performance are vital to be conducted and evaluated. The research aimed to assess the Knowledge Management System (KMS) evaluation model implemented at PT Perusahaan Listrik Negara (PLN) (Persero), a state electricity company, and found the factors and indicators to improve employee performance. The research applied a survey that collected data through a summative evaluation by using a questionnaire. The population in the research was 100 employees in PT PLN (Persero). The sampling technique was a probability, namely purposive sampling. Then, the results were examined using the SPSS program to measure the relationship of the variables under study. The collected data were also analyzed quantitatively using descriptive and inferential statistics. The analysis results show that people, process, and technology positively affect employee performance. Thus, based on the results, it can be concluded that the three main elements of KMS have a positive impact on the performance of the employees of PT PLN (Persero). It is suggested that the company takes care of their people, process, and technology to improve its performance considering the findings. It is expected that the management of PT PLN (Persero) can develop and optimize the factors that affect employee performance in using KMS for sustainable company decisions.